Study of the Prevalence of Cytomegalovirus in Children with Malignancy in Southwestern Iran from 2016-2023 - Arash Alghasi; Saeed Bitraf; Roya Salehi Kahyesh; Yasin Alidadi; Homayoun Yousefi; Manouchehr Makvandi (Iranian South Medical Journal)
Background: Cytomegalovirus (CMV) infection is one of the most common infections worldwide. This infection is especially dangerous for people with weakened immune systems and patients who have had organ transplants. This study seeks to determine the impact of cytomegalovirus infection on the treatment and survival rate of children with various types of malignancies. Materials and Methods: Information on children with malignancies and suspected cytomegalovirus infection from 2016 to 2023, whose cytomegalovirus infection was diagnosed by molecular methods, was entered into a questionnaire, and then, with the help of SPSS version 26 statistical software and the Chi-square test, the effect of the treatment of this infection on the improvement and treatment of malignancies was evaluated. Results: In this study, 54 children with positive test results and 90 children with negative test results were included, with a mean age of eight years for the positive cases and seven years for the negative cases. In children with positive test results, symptoms included fever, diarrhea, fever & diarrhea, pneumonia, and pneumonia & diarrhea, with fever and diarrhea being the most commonly reported symptoms in affected children. Most cases of CMV positivity were observed in patients with ALL. Conclusion: This study investigated the association between CMV infection and the risk of mortality from this infection in children with various malignancies. Given that CMV infection can be fatal in individuals with impaired or weak immune systems, patients with malignancies should be routinely evaluated for CMV in order to reduce the complications associated with this infection.